Lessons from a Bootcamp for Rapid Cross-skilling of Hospital Clinical Staff during the COVID-19 Pandemic - Huon Snelgrove; Indranil Chakravorty; Alice Kitt; Christopher Broom; Sarah Crabtree; Asanga Fernando; Nicholas Gosling (MedEdPublish, 2021)
The COVID-19 pandemic posed a major challenge for the UK National Health Service to scale up acute and intensive care beds at a scale never before conceived in peacetime history. To manage this upscaling, hospitals were tasked to upskill and cross-skill majority of clinical staff to be redeployed in COVID-19 clinical areas. Responding to this challenge education departments employed a variety of strategies to provide this training to staff in the space of a few weeks, as the COVID-19 pandemic surge arrived. In a University teaching hospital in London, one of the hotspots of COVID-19 in the UK during the first surge, approximately 1000 clinical staff were trained through military-style ‘Bootcamps’.